Differences in diet composition and foraging patterns between sexes of the Magellanic penguin (Spheniscus magellanicus) during the non-breeding period as revealed by δ13C and δ15N values in feathers and bone - Silva, Laura Alejandra (2014)
In diving seabirds, sexual dimorphism in size often results in sex-related differences of foraging patterns. Previous research on Magellanic penguins, conducted during the breeding season, failed to reveal consistent differences between the sexes on foraging behavior, despite sexual dimorphism. In this paper, we tested the hypothesis that male and female Magellanic penguins differ in diet and foraging patterns during the non-breeding period when the constraints imposed by chick rearing activities vanish. We used stable isotope ratios of carbon and nitrogen in feather and bone to characterize the diet and foraging patterns of male and female penguins in the South Atlantic at the beginning of the 2009-2010 and 2010-2011 post-breeding seasons (feathers) and over several consecutive breeding and migratory seasons (bone). The mean δ13C and δ15N values of feathers showed no differences between the sexes in any of the three regions considered or in the diet composition between the sexes from identical breeding regions; however, Bayesian ellipses showed a higher isotopic niche width in males at the beginning of the post-breeding season. Stable isotope ratios in bone revealed the enrichment of males with δ13C compared with females across the three regions considered. Furthermore, the Bayesian ellipses were larger for males and encompassed those of females in two of the three regions analyzed. These results suggest a differential use of winter resources between the sexes, with males typically showing a larger diversity of foraging/migratory strategies. The results also show that dietary differences between male and female Magellanic penguins may occur once the constraints imposed by chick rearing activities cease at the beginning of the post-breeding season.